Optimization of fermentation-relevant factors: A strategy to reduce ethanol in red wine by sequential culture of native yeasts - Maturano, Yolanda Paola; Mestre Furlani, Maria Victoria; Kuchen, Benjamín; Toro, Maria Eugenia; Mercado, Laura Analia; Vazquez, Fabio; Combina, Mariana (2018)
Current consumer preferences are determined by well-structured, full-bodied wines with a rich flavor and with reduced alcohol levels. One of the strategies for obtaining wines with reduced ethanol content is sequential inoculation of non-Saccharomyces and Saccharomyces cerevisiae yeasts. However, different factors affect the production of metabolites like ethanol, glycerol and acetic acid by inoculated yeasts. In order to obtain low alcohol wines without quality loss, the aims of our study were: i) to determine optimum conditions (fermentation temperature and time of permanence and initial inoculum size of the non-Saccharomyces population at the beginning of the process, prior to inoculation with S. cerevisiae); ii) to validate the optimized factors; and iii) to assess sensory quality of the wines obtained after validation. Two combinations of yeasts were used in this study: Hanseniaspora uvarum BHu9/S. cerevisiae BSc114 and Candida membranaefaciens BCm71/S. cerevisiae BSc114. Optimization of three fermentation factors that affect to non-Saccharomyces yeasts prior to S. cerevisiae inoculation was carried out using a Box-Behnken experimental design. Applying the models constructed by Response Surface Methodology, the lowest ethanol production by H. uvarum BHu9/S. cerevisiae BSc114 co-culture was obtained when H. uvarum BHu9 was inoculated 48 h 37 min prior to S. cerevisiae inoculation, at a fermentation temperature of 25 °C and at an initial inoculum size of 5 × 106 cells/mL. Lowest alcohol production with C. membranaefaciens BCm71/S. cerevisiae BSc114 was observed when C. membranaefaciens BCm71 was inoculated 24 h 15 min prior to S. cerevisiae at a fermentation temperature of 24.94 °C and at an initial inoculum size of 2.72 × 106 cells/mL. The optimized conditions of the two co-cultures were subsequently submitted to lab-scale validation. Both proposed strategies yielded ethanol levels that were significantly lower than control cultures (S. cerevisiae). Wines fermented with non-Saccharomyces/Saccharomyces co-cultures under optimized conditions were also associated with higher aromatic complexity characterized by the presence of red fruit aromas, whereas wines obtained with S. cerevisiae BSc114 were described by parameters linked with high ethanol levels.